Enhancing training motivation in the public sector in South Korea: The value of a contingency approach - KIM, Yong Hyun (Institutional Knowledge at Singapore Management University, 2014)
Public sector organisations which invest in trainingprogrammes care about their employees’ successful application of learntknowledge and skills in the workplace. The present study finds that leadersupport positively influences public sector employees’ training motivation,specifically the motivation to transfer learnt knowledge and skills to theirjobs. However, this positive relationship is moderated by employees’ priorknowledge of training content. When employees have high levels of priorknowledge of training content, leader support is not a significant influence ontheir motivation to transfer learnt knowledge and skills to their jobs. Thesefindings are derived from a survey of 335 South Korean government officials whorecently participated in a training programme that focused on performancemanagement systems. The findings suggest that leaders need to take a contingentapproach when expressing support for training programmes.